Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1101/gad.193243.112
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration ofDrosophilasensory neuron axons and dendrites is regulated by the Akt pathway involvingPtenand microRNAbantam

Abstract: Both cell-intrinsic and extrinsic pathways govern axon regeneration, but only a limited number of factors have been identified and it is not clear to what extent axon regeneration is evolutionarily conserved. Whether dendrites also regenerate is unknown. Here we report that, like the axons of mammalian sensory neurons, the axons of certain Drosophila dendritic arborization (da) neurons are capable of substantial regeneration in the periphery but not in the CNS, and activating the Akt pathway enhances axon rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
232
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(256 citation statements)
references
References 42 publications
10
232
0
Order By: Relevance
“…Similarly, the role of organelles such as the primary cilium in dendrite morphogenesis remains to be elucidated. Defects in dendrite morphogenesis have been observed in neurons with conditional deletion of cilia (Song et al, 2012), but the underlying signaling mechanisms remain poorly characterized. The authors suggest that Wnt signaling might be dysregulated, thereby mediating aberrations in dendrite patterning.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the role of organelles such as the primary cilium in dendrite morphogenesis remains to be elucidated. Defects in dendrite morphogenesis have been observed in neurons with conditional deletion of cilia (Song et al, 2012), but the underlying signaling mechanisms remain poorly characterized. The authors suggest that Wnt signaling might be dysregulated, thereby mediating aberrations in dendrite patterning.…”
Section: Discussionmentioning
confidence: 99%
“…Mature dendrites have a predominantly minus--ends--out microtubule array 18 , nevertheless recent studies identified that anterograde microtubule polymerization events in mature neurons can initiate or extend branches or modulate the size of dendritic spines 19,20 . In addition, the re--initiation of growth and branch formation following injury uses upregulation of microtubule polymerization and polarization in the anterograde direction 21 .…”
mentioning
confidence: 99%
“…Furthermore, the manipulation of the JIP1-AKT axis could represent a potential route for promoting nerve regeneration. There is already evidence that JIP1 promotes regeneration of adult mouse dorsal root ganglion neurons (Barnat et al, 2010) and a number of studies have proposed a role for AKT-mediated signalling in axonal regeneration (Namikawa et al, 2000;Kim et al, 2011;Song et al, 2012).…”
Section: Discussionmentioning
confidence: 99%